"Siła kojąca" czy "narkotyk drażniący"? Prus i Orzeszkowa wobec pisarstwa Eugeniusza Sue = "A Soothing Power" or "An Irritating Drug"? Prus and Orzeszkowa in the Light of Eugene Sue`s Writing - Kuniczuk-Trzcinowicz, Agnieszka; Narolska, Aneta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The theme of the article is the reception of Eugene Sue`s writing in the era of positivism. Boleslaw Prus and Eliza Orzeszkowa`s critical statements and selected literary have been the focus of theresearch. The relationships between Orzeszkowa`s "Sylwek Cmentarnik" and Sue`s "Children of Love" have been thoroughly discussed.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); Prus, Bolesław (pseud.; 1847-1912); Orzeszkowa, Eliza (1841-1910); literatura francuska - krytyka